UV SPECTROSCOPY DETERMINATION OF CILAZAPRIL AND HYDROCHLOROTHIAZIDE ACTIVE AGENTS USED IN THE TREATMENT OF HYPERTENSION - AKTAŞ, A. Hakan (Universal Journal of Pharmaceutical Research, 2021)
Background: Antihypertensive and diuretic drugs are widely used in patients to regulate high blood pressure. Objective of current study was to prepare various cilazapril and hydrochlorothiazide mixtures, to create a matrix effect in the drug and to determine the determination of these active substances in drug samples after optimum conditions. Method: In the spectrophotometric method, 100 mgL−1 solutions were prepared in cilazapril, hydrochlorothiazide in methanol + 0.1 m HCL solvent and then mixtures of these solutions were prepared between specific ppm. The absorbance’s of the solvent against the blind were read at 0.1 nm intervals. After the mixture, tablet (drug) sample was prepared and chemometrics methods were applied to the values obtained by saving the absorbance values. Results: It was observed that the main component analysis applied as a result of spectrophotometric determination of various mixtures of cilazapril and hydrochlorothiazide used in the study gave correct results. These results were validated using various chemometric parameters. Conclusion: The proposed chemometric method can be used in routine analysis in industrial laboratories. Peer Review History: Received 5 October 2020; Revised 13 November; Accepted 26 December; Available online 15 January 2021 Academic Editor: Prof. Kumud Upadhyaya, Kumaon University, Nainital, UK, India, upkuupku@gmail.com Reviewer(s) detail: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Dr. U. S. Mahadeva Rao , Universiti Sultan Zainal Abidin, Terengganu Malaysia, raousm@gmail.com